Answer:
To find the y-coordinate for the solution to the system of equations {6x - 3y = -7, 2x + 3y = -9, we can use the method of substitution or elimination.
Let's use the method of elimination to solve the system of equations:
Step 1: Multiply the second equation by 2 to eliminate the x variable:
2(2x + 3y) = 2(-9)
4x + 6y = -18
Step 2: Add the first equation and the modified second equation to eliminate the x variable:
(6x - 3y) + (4x + 6y) = -7 + (-18)
10x + 3y = -25
Step 3: Solve the resulting equation for y:
10x + 3y = -25
3y = -10x - 25
y = (-10x - 25) / 3
The y-coordinate for the solution to the system of equations is (-10x - 25) / 3.
Step-by-step explanation: